Generation of AE signals and its waveform characteristics of gas leakage emanated on pipe with specific defects of different geometrical shapes - Laodeno, Rem Nunez (Philippine Engineering Journal)
Acoustic Emission testing method is now widely recognized as the most appropriate tool to determine the flaws from material structure as a non-destructive technique (NDT). In this study, we have used this method to determine the characteristics of the generated AE signals and analyze its waveforms relative to time and frequency domain at various gas pressures. We have considered four different geometrical shapes of pinhole such as straight-type, stepwise-type, slit-type and cone-type. All these defects were artificially made on conventional pipe (JIS SGP20A) commonly used for gas pipeline. The experimental results described common behavior of AE waveforms for each type of the specific defect. As in the case of straight type pinhole, the pressure shock occurred above the critical pressure at 220kPa and eventually screech tone was generated while pressure increases until it reached to 500kPa primarily because of unstable gas flow and turbulent flow. For stepwise-type, we observed different characteristics of AE waveform. Apparently, a monotonic increase of amplitude took place at the onset since self excited vibration of the acoustic signals within the flow structure occurred. Also, sudden dropped of amplitude the critical pressure was recorded. On the other hand, the slit-type defect showed a rapid fluctuation of acoustic signals because of strong energy released by gas leak so its amplitude became higher in magnitude. Lastly, for cone-type pinhole showed other distinct characteristics at which unusual sound was observed. It seems that this type of orifice have similar pattern with that of stepwise pinhole relative to its peak frequency values. In general, a unique behavior of acoustic signals was mainly caused by the large scale instability of flow of the gas leakage emanated on specifically defective pipe with various geometrical shapes.